Encouraging household waste separation: Can social comparison help? - Cardadeiro, E.; Roseta-Palma, C.; Laneiro, T. (European Review of Business Economics, 2023)
As more people move to urban areas, larger flows of solid waste are generated, bringing about significant challenges in municipal solid waste management. Implications of management failure can be serious for human health and for the environment, and landfills are not a sustainable solution. European legislation makes it clear that business-as-usual is not good enough and sets ambitious targets for the coming years. In Portugal, waste separation at source is far below the desired levels, highlighting the need for policy change. Other authors have attempted to stimulate resource conservation, especially for water and electricity, using social comparison nudges. In this paper, we describe a similar field experiment for waste, developed in 6 parishes (“freguesias”) in the north of Portugal; treatment households received a message comparing their parish’s per capita deposition of sorted waste in existing collection bins to that of a neighboring parish or to higher environmental targets. Finally results, however, are contradictory.